2015
DOI: 10.5021/ad.2015.27.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5% Imiquimod Cream on Vulvar Intraepithelial Neoplasia in Korea: Pilot Study

Abstract: BackgroundVarious therapeutic options, including surgery, electrocautery, cryotherapy, 5-fluorouracil treatment, laser therapy, radiotherapy, photodynamic therapy, and interferon-α/γ injection, have been employed to treat vulvar intraepithelial neoplasia (VIN) with varying degrees of success. To truly cure VIN, human papillomavirus elimination is considered important.ObjectiveTo investigate the efficacy of 5% imiquimod cream used to treat VIN in Korean patientsMethodsWe performed a prospective, uncontrolled, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Dermoscopic features of VIN have rarely been described. Ten to 15% of cases of VIN are hyperpigmented . Ronger‐Savle et al .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Dermoscopic features of VIN have rarely been described. Ten to 15% of cases of VIN are hyperpigmented . Ronger‐Savle et al .…”
mentioning
confidence: 90%
“…The term ‘vulvar intraepithelial neoplasia’ refers to a variety of pathological conditions with different severity grades and a prevalence of 1 case per 100 000 women/year . Histopathologically, VIN represents an in situ SCC of the vulva, with moderate‐to‐severe dysplasia …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IQ was found to also exhibit antitumor effects against different malignancies such as prostate and urothelial cell carcinoma (30, 31). Clinical trials further demonstrated that IQ is effective in the treatment of vulvar, cervical, and vaginal intraepithelial neoplasias (3234). IQ exhibits antitumor activity presumably by inducing apoptosis through direct and indirect pathways (35).…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, although, there could be lack of response following imiquimod usage, which has been attributed to regional drug resistance. [6] Recently, intralesional usage of 5-FU at weekly intervals has been utilized for GW. [34] I, however, utilized 5-FU on a monthly basis.…”
mentioning
confidence: 99%